FROM MATERNITY TO PARENTAL LEAVE: A SHIFT TOWARDS GENDER EQUALITY IN THE WORKPLACE - Yogatama, Ahmad Nizar (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The findings of this study, which utilized Media Content Analysis, indicate that the implementation and expansion of paternity leave policies are crucial for promoting the well-being of fathers, mothers, and families, as well as advancing gender equality and supporting population health. The implications presented in this study are based on an in-depth analysis of media content. The findings highlight the significance of addressing cultural and societal obstacles that impede fathers' engagement in caregiving activities. Additionally, it emphasizes the need to establish inclusive workplace policies that facilitate a healthy work-life balance for fathers. Lastly, it underscores the importance of promoting a transformation in societal attitudes towards shared parenting responsibilities. These implications are crucial for advancing the involvement of fathers in caregiving and fostering a more equitable and supportive society. Through the implementation and expansion of paternity leave policies, societies have the potential to augment the holistic welfare of families, foster gender parity, and make significant contributions to the enhancement of population health outcomes.